Case Report: A False Negative Case of Anti-Yo Paraneoplastic Myelopathy - Bartley, Christopher M.; Parikshak, Neelroop N.; Ngo, Thomas T.; Alexander, Jessa A.; Zorn, Kelsey C.; Alvarenga, Bonny D.; Kang, Min K.; Pedriali, Massimo; Pleasure, Samuel J.; Wilson, Michael R. (Frontiers in Neurology, 2021)
The development of autoimmune antibody panels has improved the diagnosis of acute and subacute paraneoplastic neurological disorders (PNDs) of the brain and spine. Here, we present a case of a woman with a history of breast cancer who presented with sensory ataxia progressing over eighteen months. Her examination and diagnostic studies were consistent with a myelopathy. Metabolic, infectious, and autoimmune testing were nondiagnostic. However, she responded to empirical immunosuppression, prompting further workup for an autoimmune etiology. An unbiased antibody screen utilizing phage display immunoprecipitation sequencing (PhIP-seq) identified antibodies to the anti-Yo antigens cerebellar degeneration related protein 2 like (CDR2L) and CDR2, which were subsequently validated by immunoblots and cell-based overexpression assays. Recent evidence suggests that CDR2L is likely the primary antigen in anti-Yo paraneoplastic cerebellar degeneration, but anti-Yo myelopathy is poorly characterized. By immunostaining, we detected neuronal CDR2L protein expression in the murine and human spinal cord. This case demonstrates the diagnostic utility of unbiased assays in patients with suspected PNDs, supports prior observations that anti-Yo antibodies can be associated with isolated myelopathy, and implicates antibodies to CDR2L in myelopathy.